اختبار منحنی (Armey) ومنهجية (ARDL) لتحليل حجم الإنفاق الحكومي الأمثل للنمو الاقتصادي في العراق للمدة (٢٠٠٤-٢٠٢١). - أحمد, م. د. هاوژین خسرەو (Sulaimani Journal for Humanities, 2023)
This research seeks to analyze and estimate the optimal size of government spending that maximizes economic growth in Iraq, and to analyze the possibility of testing the (Armey) curve hypothesis and by applying it to data on the Iraqi economy over the period (2004-2021). The results showed that the relationship between the size of government spending and economic growth in Iraq is non-linear and supports the existence of the (Armey) curve. The result of the regression model with distributed lag periods (ARDL) also showed that there is a short and long-term relationship and cointegration between the variables used in the standard model, as the research found. The optimal size of government spending has reached the limits of (18.73%) as a percentage of GDP, which is less than the average year's spending as a percentage of GDP during the research period, which requires a necessary reduction in the size of government spending.
Keywords: optimal government spending; economic growth; Armey curve; ARDL model